If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x/6+3.7=6.3
We move all terms to the left:
x/6+3.7-(6.3)=0
We add all the numbers together, and all the variables
x/6-2.6=0
We multiply all the terms by the denominator
x-(2.6)*6=0
We add all the numbers together, and all the variables
x-15.6=0
We move all terms containing x to the left, all other terms to the right
x=15.6
| 3x+9=2.7 | | w/3+5=4 | | 17-5x=5-2x | | 6-5x=5x+12 | | 0=y^2/7-y | | 14y-6y=32 | | 6-4x=5x+12 | | x/8=4/7 | | 16x-2=13x-9 | | -19t–19=19 | | 0=x^2+9x+144 | | 3n÷4=22 | | 6x+29=7x+10 | | (x+4)=16 | | (11x+5)+(8x-15)=90 | | 8m-7m=16 | | 13x+23x+13x+23x=360 | | 4x+9+5x+x+x=360 | | 12x-3+10x+15=180 | | -190=10w | | -26=2z-2 | | 5t-3t-2+6=2t-3t-4-t | | 10v+8v=18 | | .10*x=15 | | 8x-2x=132 | | 9xY=450 | | -x=+20=x-4 | | 3y+5=82 | | 194-38/6=s | | 2.2/X x =2x-3 | | 5m-1=-10m-19 | | (D^3+6D^2+12D+8)*y=0 |